Papa daisuki - Braun, Sébastien (Tokuma Shoten, 2007)
A father bear and his cub spend the whole day together
In japan. Schr.
Keywords: Father and child / Juvenile fiction; Bears / Juvenile fiction; Day / Juvenile fiction